Transmisión de datos móviles en sistemas distribuidos para el control de congestión en la red wifi de la Universidad Técnica de Babahoyo. - López Ledesma, Anddy Christopher (2023)
The growing demand for bandwidth in the WiFi network of the Technical University of Babahoyo has generated congestion problems that affect the quality of service and the user experience. The lack of a congestion control system in the university's WiFi network further aggravates this problem. Therefore, it is necessary to implement a system that allows constant monitoring of data traffic in the network, early detection of congestion problems and the implementation of measures to avoid system collapse. The general objective is to implement a distributed system for congestion control in the WiFi network of the Technical University of Babahoyo using advanced mobile data transmission techniques in distributed systems. A bibliographic, applied and experimental research was carried out and the InSSiDer tool was used to measure the traffic and congestion of the PorTiUtb network to carry out this project and to be able to propose possible recommendations to the problem presented.